Characterization and Treatment Study of A handcraft Brass Trumpet From Dhamar Museum, Yemen - Megahed, Mohamed; Abdelbar, Mohamed M. (Archeomatica, 2018)
Brass is more malleable and has better acoustic properties than pure copper or zinc; consequently, it is used in a variety of musical instruments, including trumpets, trombones, bells, and cymbals. The overall goal of this work is to represent an analytical and conservation study of brass Trumpet from the handcrafts collection of Dhamar museum in Yemen. Metallographic examination and scanning electron microscope were performed to identify the microstructure of the alloy. Energy dispersive spectroscopy EDS and x-ray fluorescence (XRF) were used to identify the alloy composition used for manufacturing the musical instruments and the solder joints. X-ray diffraction (XRD) was used for the identification of the crystalline corrosion products. Finally, exploited the previous info., in a systemic treatment and conservation for the selected object.